Solusi Terpadu Relaksasi Otot Dan Murotal Al-Qur’an Dalam Mengelola Nyeri Dismenore Pada Remaja - Winarni, Winarni; Yuyun, Yuyun (Jurnal Pengabdian Masyarakat (Jupemas), 2026)
Dysmenorrhea affects nearly 90% of Indonesian women, with 14% reporting impaired daily functioning due to menstrual pain. Among adolescents, emotional instability and insufficient understanding of the menstrual process contribute to the high prevalence of primary dysmenorrhea. Several non-pharmacological interventions have been explored, including Thibbun Nabawi modalities that combine Qur’anic recitation (murottal) with progressive muscle relaxation. This approach is cost-effective, non-invasive, and easily self-administered. Educational initiatives at SMART Community-Based Youth Organization are urgently needed due to the predominant reliance on pharmacological treatments and limited knowledge of safe and effective non-pharmacological pain management. This community engagement program aims to enhance adolescents’ understanding of menstrual disorders, particularly dysmenorrhea, and to introduce practical, accessible, and side-effect-free pain management techniques through muscle relaxation and Qur’anic murottal.